Evaluation of the Thermal Energy Potential of Waste Products from Fruit Preparation and Processing Industry - Bača, Petr; Mašán, Vladimír; Vanýsek, Petr; Burg, Patrik; Binar, Tomáš; Suchý, Pavel; Vaňková, Lenka (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2024)
In the context of a changing climate and increasing efforts to use renewable energy sources and waste materials and to green the environment, new sources and technologies for energy recovery from waste are being sought. This study evaluates the possibilities of energy generation potential from waste products of fruit species used in the food processing industry. The results indicate good potential for energy use of materials from fruit processing due to low input moisture content of around 15 wt. %, an average energy lower heating value (LHV) of 16.5 MJ.kgMINUS SIGN 1, an average low ash content of 4.9% and meeting most of the emission limits of similar biofuels. Elemental analysis and combustion residue studies indicate safe operation within existing standards. The results of our analyses and experience from similar studies allow us to recommend most of the studied waste materials for energy generation use directly in processing plants at the local level.
Keywords: circular economy; energy mix; heating value; fruit stone; nut shell; pomace